Activity Modes in Thalamocortical Relay Neurons are Modulated by Gq/G11 Family G-proteins – Serotonergic and Glutamatergic Signaling - Coulon, Philippe; Kanyshkova, Tatyana; Broicher, Tilman; Munsch, Thomas; Wettschureck, Nina; Seidenbecher, Thomas; Meuth, Sven G.; Offermanns, Stefan; Pape, Hans-Christian; Budde, Thomas (Frontiers in Cellular Neuroscience, 2010)
In thalamocortical relay (TC) neurons, G-protein-coupled receptors play an important part in the control of activity modes. A conditional Gαq knock out on the background of a constitutive Gα11 knock out (Gαq/Gα11 -/-) was used to determine the contribution of Gq/G11 family G-proteins to metabotropic serotonin (5-HT) and glutamate (Glu) function in the dorsal part of the lateral geniculate nucleus (dLGN). In control mice, current clamp recordings showed that α-m-5-HT induced a depolarisation of Vrest which was sufficient to suppress burst firing. This depolarisation was concentration-dependent (100 μM: +6 ± 1 mV, n = 10; 200 μM: +10 ± 1 mV, n = 7) and had a conditioning effect on the activation of other Gαq-mediated pathways. The depolarisation was significantly reduced in Gαq</sub/Gα11</sub -/- (100 μM: 3 ± 1 mV, n = 11; 200 μM: 5 ± 1 mV, n = 6) and was apparently insufficient to suppress burst firing. Activating Gαq coupled muscarinic receptors affected the magnitude of α-m-5-HT induced effects in a reciprocal manner. Furthermore, the depolarising effect of mGluR1 agonists was significantly reduced in Gαq/Gα11 -/- mice. Immunohistochemical stainings revealed binding of 5-HT2CR- and mGluR1α-, but not of 5-HT2AR-specific antibodies in the dLGN of Gαq/Gα11 -/- mice. In conclusion, these findings demonstrate that transmitters of ascending brainstem fibres and corticofugal fibres both signal via a central element in the form of Gq/G11-mediated pathways to control activity modes in the thalamocortical system.